PENGARUH KOMPETENSI, INDEPENDENSI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI PADA INSPEKTORAT KEPOLISIAN DAERAH KALIMANTAN BARAT - Jati, Lusi Rosita (MAKSI UNTAN, 2021)
This study aims to know the effect of competence, independence, andÂ  leadership style on auditor performance with culture as a moderating variable. The population in this study is all officers of The Police Supervision Inspectorate in West Kalimantan. The number of respondents is as many as the population, namely 31 questionnaires. Considering the total population is less than 100 respondents, therefore, the sampling method used is the census method, in which questionnaires are distributed to all populations. The data analysis techniques used in this study are Bifilar Regression Analysis and Moderate Regression Analysis (MRA). The results of this research hypothesis testing indicate that competence, independence, and leadership style have a positive and significant effect on auditor performance. Meanwhile, organizational culture has not been able to moderate the relationship among competence, independence, and leadership style and auditor performance.